Near‐Zero Power MOF‐Based Sensors for NO2 Detection. (13th September 2020) - Small, Leo J.; Henkelis, Susan E.; Rademacher, David X.; Schindelholz, Mara E.; Krumhansl, James L.; Vogel, Dayton J.; Nenoff, Tina M.
Abstract: Detection and capture of toxic nitrogen oxides (NO x ) is important for emissions control of exhaust gases and general public health. The ability to directly electrically detect trace (0.5–5 ppm) NO2 by a metal–organic framework (MOF)‐74‐based sensor at relatively low temperatures (50 °C) is demonstrated via changes in electrical properties of M‐MOF‐74, M = Co, Mg, Ni. The magnitude of the change is ordered Ni > Co > Mg and explained by each variant's NO2 adsorption capacity and specific chemical interaction. Ni‐MOF‐74 provides the highest sensitivity to NO2 ; a 725× decrease in resistance at 5 ppm NO2 and detection limit <0.5 ppm, levels relevant for industry and public health. Furthermore, the Ni‐MOF‐74‐based sensor is selective to NO2 over N2, SO2, and air. Linking this fundamental research with future technologies, the high impedance of MOF‐74 enables applications requiring a near‐zero power sensor or dosimeter, with the active material drawing <15 pW for a macroscale device 35 mm 2 with 0.8 mg MOF‐74. This represents a 10 4 –10 6 × decrease in power consumption compared to other MOF sensors and demonstrates the potential for MOFs as active components for long‐lived, near‐zero power chemical sensors in smart industrial systems and the internet of things. Abstract : Metal–organic frameworks (MOFs) enable near‐zero power detection of toxic NO2 . As the internet of things has expanded society's demand to sense toxic gases for public health, the need for long‐lived, near‐zero power, remote chemical sensors has increased. This report highlights how MOF‐74 can serve as the active material in a near‐zero power sensor for long‐lived, remote detection of NO2 .